Mathematical Model and Numerical Simulation of hydrothermal Coupling for Unsaturated Soil Subgrade in the Seasonal Frozen Zone. Issue 3 (April 2021) - Wang, Cong; Ma, Zipeng
Abstract: The subgrade in the seasonal frozen zone is easy to induce uneven settlement, frost heave and thaw settlement under the action of environmental factors such as precipitation, evaporation, radiation, etc. The subgrade is mostly unsaturated soil. In non-saline soil areas, its diseases are mostly related to moisture migration and phase change in the soil. In order to study the moisture migration and temperature distribution of the unsaturated soil subgrade in the seasonal frozen zone, a hydrothermal coupling mathematical model was established. Based on the mathematical model, the hydrothermal coupling numerical simulation was carried out by using the COMSOL Multiphyscis finite element program, Given the basic parameters and variables, the model was solved by assigning the same initial and boundary conditions as the field test, and the simulation results were compared with the field test results to obtain very satisfactory temperature simulation results and a good fit between the moisture migration results and the field test values, proving the reliability of the mathematical model.